Impact of rye-based evening meals on cognitive functions, mood and cardiometabolic risk factors: a randomized controlled study in healthy middle-aged subjects - Sandberg, Jonna C. (Nutr J, 2018)
BACKGROUND: Whole grain (WG) intake is associated with reduced risk of obesity, type 2 diabetes and cardiovascular disease, whereas type 2 diabetes increases the risk of cognitive decline and dementia. The purpose of this study was to investigate the effects of short-term intervention with WG rye on cognitive functions, mood and cardiometabolic risk markers in middle-aged test subjects. METHOD: Rye-based breads were provided to 38 healthy test subjects (aged 52-70y) during three consecutive days in a crossover study design, using white wheat flour bread (WWB) as a reference. The rye-based bread consisted of a WG rye kernel/flour mixture (1:1 ratio) supplemented with resistant starch type 2 (RS2) (RB + RS2). The last bread portion was ingested at 2100 h, and cognitive function, mood and cardiometabolic risk markers were determined the following morning, 11 − 14 h post intake. RESULTS: In comparison to WWB, the RB + RS2 product increased ratings of mood parameters (valance, P < 0.001; activation P < 0.05). No differences were seen in the cognitive tests depending on intervention (P > 0.05). RB + RS2 increased insulin sensitivity (P < 0.05), fasting levels of gut hormones (PYY, P < 0.05; GLP-2, P < 0.01) and fasting concentrations of plasma acetate, butyrate and total SCFA (P < 0.001). In contrast, fasting levels of IL − 1β were decreased (P < 0.05). Insulin sensitivity was positively correlated with working memory test performance (P < 0.05). CONCLUSIONS: This study display novel findings regarding effects of WG rye products on mood, and glucose and appetite regulation in middle-aged subjects, indicating anti-diabetic properties of WG rye. The beneficial effects are suggested to be mediated through gut fermentation of dietary fiber in the RB + RS2 product. TRIAL REGISTRATION: The study was retrospectively registered at ClinicalTrials.gov, register number NCT03275948. Registered September 8 2017.